What, where, and when: Spatial-temporal distribution of macro-litter on the seafloor of the western and central Mediterranean sea - Alessandro Cau; Alice Sbrana; Simone Franceschini; Fabio Fiorentino; Maria Cristina Follesa; Francois Galgani; Germana Garofalo; Olivia Gerigny; Adriana Profeta; Paola Rinelli; Mario Sbrana; Tommaso Russo (Environmental Pollution, 2024)

Commercial sharks under scrutiny: Baseline genetic distinctiveness supports structured populations of small-spotted catsharks in the Mediterranean Sea - Riccardo Melis; Laura Vacca; Alessia Cariani; Laura Carugati; Alessandro Cau; Charis Charilaou; Simone Di Crescenzo; Alice Ferrari; Maria Cristina Follesa; Farid Hemida; Sarah Helyar; Sabrina Lo Brutto; et al. (Frontiers in Marine Science, 2023)
The present study, based on microsatellite markers, describes a population genetic analysis of the small-spotted catshark Scyliorhinus canicula (Linnaeus, 1758), representing one of the most abundant and commonly caught cartilaginous fishes in the Mediterranean Sea and adjacent areas. The analyses were performed to unravel the genetic features (variability, connectivity, sex-biased dispersal) of their relative geographic populations, both at the small (around the coast of Sardinia, Western Mediterranean Sea) and at a larger spatial scale (pan-Mediterranean level and between the Atlantic Ocean and the Mediterranean Sea). Individual clustering, multivariate and variance analyses rejected the hypothesis of genetic homogeneity, with significant genetic differences mainly within the Mediterranean between the Western and Eastern basins, as well as between the Mediterranean and the NE Atlantic Ocean. In detail, our results seem to confirm that the Strait of Gibraltar could not represent a complete barrier to the exchange of individuals of small-spotted catshark between the Atlantic Ocean and the Mediterranean Sea. In the latter area, a complex genetic structuring for S. canicula was found. Apart from differences among the Western, Eastern and Adriatic sites, within the Western basin the small-spotted catsharks around Sardinian waters are strongly differentiated from all others (both from the eastern Tyrrhenian Sea and southernmost part of the Algerian basin) and are demographically stable. Several possible mechanisms, both biological and abiotic (e.g., migratory behavior, waterfronts, and oceanographic discontinuities), are discussed here to explain their peculiar characteristics. Overall, the genetic data presented, both at the local and regional level, could represent a baseline information, useful for the temporal monitoring of populations, and to assess the effects of present or future fishing/management/conservation measures.

Late Quaternary sedimentary record of estuarine incised-valley filling and interfluve flooding: The Manfredonia paleovalley system (southern Italy) - Alessandro Amorosi; Luigi Bruno; Massimo Caldara; Bruno Campo; Simone Cau; Vincenzo De Santis; Andrea Di Martino; Wan Hong; Giorgio Lucci; Claudio Pellegrini; Veronica Rossi; Irene Sammartino; et al. (Marine and Petroleum Geology, 2023)

Ask the shark: blackmouth catshark (Galeus melastomus) as a sentinel of plastic waste on the seabed - Alice Sbrana; Alessandro Cau; Davide Cicala; Simone Franceschini; Tommaso Giarrizzo; Maria Flavia Gravina; Alessandro Ligas; Giulia Maiello; Marco Matiddi; Antonio Parisi; Paolo Sartor; Mario Sbrana; et al. (Marine Biology, 2022)
The presence of plastic waste in the marine environment has driven the scientific community to make significant efforts to study and mitigate its possible effects. One of the critical aspects is to determine if and how an increase in ingestion events may occur as a result of the accumulation of plastic waste on the seabed. In this study, G. melastomus is examined for its ability to indirectly provide information on the amount of macroplastics accumulating on the seafloor. Plastic ingestion is explored by describing the feeding habits of the species, which have the potential to provide very useful information regarding biological or ecological issues. The diet of G. melastomus mainly consisted of cephalopods, bathypelagic fishes, and decapod crustaceans, increasing in diversity during growth. The generalist-opportunistic feeding behaviour of this species leads to the incidental ingestion of plastic particles ( N = 47, with a mean (± SD) of 1.47 ± 0.28 per specimen) which can be indirectly associated to the presence of macroplastics on the seafloor. Indeed, our results indicate a significant relationship between the amount of macroplastics present on the seabed and the frequency of ingestion of plastic particles by blackmouth catshark. We propose G. melastomus as an excellent candidate for developing a valid monitoring strategy for the presence of plastics on the seabed, as requested by the EU Marine Strategy Framework Directive.

Eating Near the Dump: Identification of Nearby Plastic Hotspot as a Proxy for Potential Microplastic Contamination in the Norwegian Lobster (Nephrops norvegicus) - Simone Franceschini; Alessandro Cau; Lorenzo D’Andrea; Maria Cristina Follesa; Tommaso Russo (Frontiers in Marine Science, 2021)
Plastic waste dumped in the marine environment has severe ecological, social and economic impacts. In recent years, a series of scientific studies documented the contamination by macroplastic and its impact on marine organisms through the accidental ingestion of microplastics, which also originate from the degradation of macroplastic. However, the relationship between the spatial distribution of marine litter and the ingestion of plastics by organisms have never been related. In this work, we aimed to investigate, through a modeling approach, the relations between potential sources of microplastic particles (i.e., seafloor macroplastic accumulation hotspots detected by means of trawl surveys), and the ingestion by the benthic crustacean Norwegian lobster ( Nephrops norvegicus ). According to the literature, N. norvegicus is characterized by a sedentary behavior and therefore it has been highlighted as a proficient sentinel species for local microplastic contamination. Despite no significant relation has been found between microplastic ingestion and the local presence of seafloor macroplastic, it seems that proximity to hotspots of macroplastic accumulation is significantly related to microplastics ingestion. These results highlight important considerations on the fate of plastic in the marine environments with significant impacts on biota and the quality of the product caught at sea.